Summary of the first inaugural joint meeting of the International Consortium for scoliosis genetics and the International Consortium for vertebral anomalies and scoliosis, March 16–18, 2017, Dallas, Texas. Issue 1 (21st November 2017) - Giampietro, Philip F.; Pourquie, Olivier; Raggio, Cathy; Ikegawa, Shiro; Turnpenny, Peter D.; Gray, Ryan; Dunwoodie, Sally L.; Gurnett, Christina A.; Alman, Benjamin; Cheung, Kenneth; Kusumi, Kenro; Hadley‐Miller, Nancy; et al.
Abstract : Scoliosis represents the most common musculoskeletal disorder in children and affects approximately 3% of the world population. Scoliosis is separated into two major phenotypic classifications: congenital and idiopathic. Idiopathic scoliosis is defined as a curvature of the spine of 10° or greater visualized on plane radiograph and does not have associated vertebral malformations (VM). "Congenital" scoliosis (CS) due to malformations in vertebrae is frequently associated with other birth defects. Recently, significant advances have been made in understanding the genetic basis of both conditions. There is evidence that both conditions are etiologically related. A 2‐day conference entitled "Genomic Approaches to Understanding and Treating Scoliosis" was held at Scottish Rite Hospital for Children in Dallas, Texas, to synergize research in this field. This first combined, multidisciplinary conference featured international scoliosis researchers in basic and clinical sciences. A major outcome of the conference advancing scoliosis research was the proposal and subsequent vote in favor of merging the International Consortium for Vertebral Anomalies and Scoliosis (ICVAS) and International Consortium for Scoliosis Genetics (ICSG) into a single entity called International Consortium for Spinal Genetics, Development, and Disease (ICSGDD). The ICSGDD is proposed to meet annually as a forum to synergize multidisciplinary spine deformity research.